Protein profiling of osteosarcoma tissue and soft callus unveils activation of the unfolded protein response pathway - Parunya Chaiyawat (2019)
© 2019 Spandidos Publications. All rights reserved. Oncogenic drivers of osteosarcoma remain controversial due to the complexity of the genomic background of the disease. There are limited novel therapeutic options, and the survival rate of patients with osteosarcoma has not improved in decades. Genomic instability leads to complexity in various pathways, which is potentially revealed at the protein level. Therefore, the present study aimed to identify the mechanisms involved in the oncogenesis of osteosarcoma using proteomics and bioinformatics tools. As clinical specimens from patients are the most relevant disease-related source, expression patterns of proteins in osteosarcoma tissues were compared with soft tissue callus from donors containing high numbers of osteoblastic cells. Two-dimensional electrophoresis and liquid chromatography.tandem mass spectrometry (LC-MS/MS) successfully identified 33 differentially expressed proteins in the osteosarcoma tissues compared with the soft tissue callus. Among these proteins, 29 proteins were significantly upregulated in osteosarcoma. A functionally grouped network of the overexpressed proteins, that was created using the ClueGo and CluePedia applications, demonstrated that the unfolded protein response (UPR) pathway was activated mainly through the activating transcription factor 6 arm in osteosarcoma. The results of proteomics analysis were confirmed by elevated expression of UPR-related chaperone proteins, including 78 kDa glucose-related protein (GRP78), endoplasmin, calreticulin and prelamin-A/C, in the patient-derived primary cells and osteosarcoma cell lines. Furthermore, the expression of GRP78, a master regulator of the UPR, was enhanced in the osteosarcoma tissues of patients that were resistant to double regimen of doxorubicin and a platinum-based drug. The findings of the present study suggest that targeting the UPR pathway may be promising for the treatment of osteosarcoma.